Etika Bertetangga Menurut Islam (Studi Kasus di Kelurahan Harjosari I Gang Budi Kota Medan) - Ditha Damayanti; Junaidi Junaidi; Husna Sari Siregar (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2022)
Ethics is usually closely related to moral words which are terms from Latin, namely mos and in its plural form mores, which also means customs or ways of life of a person by doing good deeds (decency) and avoiding bad actions. It is closely related to socializing between humans and other communities, especially those in their environment which are very concerned, especially ethics in neighbors. Neighbor ethics in Islam is an obligation that must be carried out by every Muslim, both towards others and non-Muslims. This research has two problem formulations, namely: 1) How is Neighbor Ethics According to Islam? 2) How is the Application of Neighbor Ethics in Islam in the Village of Harjosari I Gang Budi? The results of research on Neighbor Ethics According to Islam are neighboring manners in Islam are guidelines and ethics in neighbors that need to be considered by Muslims. Neighbors are people who are around us who need to be respected and needed as well as possible. In Islamic teachings, the command to do good to neighbors is juxtaposed with the command to worship Allah and the prohibition of associating partners.